Analysis of Excise Policy on Sweetened Packaged Drinks (MBDK): Consumer Protection Legal Perspective - Singgih Sasono, Wasis; Isharyanto, Isharyanto (CV. Inara, 2024)
This research aims to analyze health policies related to excise on sugary drinks and packaging labeling regulations, with a focus on public health implications in Indonesia. Normative research method to analyze Consumer Protection Laws and regulations from other countries that have implemented excise taxes on sweet drinks in an effort to reduce excessive sugar consumption. Supporting data from other countries includes the implementation of excise tax on sugary drinks, its impact on people's consumption patterns, and evaluation results related to reducing the prevalence of diabetes. This research uses a comparative approach to evaluate the effectiveness of sugary drink excise policies and labeling regulations on product packaging in reducing sugar consumption in various country contexts. Countries that implement excise taxes on sweet, high-calorie drinks have succeeded in reducing the prevalence of diabetes by influencing consumer behavior to choose products with lower sugar content. Countries that have implemented excise taxes on sweet, high-calorie drinks generally have a significant positive impact on reducing the prevalence of diabetes in society because they influence people's purchasing behavior to prefer healthier foodstuffs (lower sugar content). Therefore, legal reconstruction is needed regarding the application of excise and labeling regulations on product packaging regarding sugar content information with certain classifications for sweet drinks in order to reduce the prevalence of diabetes in Indonesia. It is hoped that the results of this research will provide insight to the Indonesian government in developing effective strategies to reduce the prevalence of sugar-related diseases and improve overall public health.